DESAIN antena mikrostrip jajaran genjang pita-C untuk aplikasi sensor synthetic aperture radar (SAR) - Ruri Oktavia (Department of Physics – Universitas Negeri Padang UNP, 2016)
Remote sensing technology sensor using synthetic aperture radar (SAR) is a type of radar sensors using methods photographing area or object being observed. SAR sensors require an antenna with a light and simple specification. Microstrip antenna has the advantage of physically simpler and easily manufactured. Parallelogram shape microstrip antenna using microstrip line is simpler and has a bandwidth is wider than the rectangular microstrip antenna using a proximity coupling. The purpose of this study is to produce a parallelogram microstrip antenna capable of working at a frequency of 5 GHz. This study simulate microstrip antenna design parallelogram. The simulation was performed by varying the dimensions of the antenna. The influence of the dimensions of the antenna to antenna characteristics are used as a reference to get the dimensions of the antenna and antenna characteristics parallelogram for SAR applications. The device used in this simulation is IE3D software with the type of substrate Nippon Pillar Packing (NPC-H220A), the dielectric constant of 2.17, thickness of 1.6 mm and loss δ = 0.0005. From this research can be presented three result. First, measure the dimensions of a single microstrip antenna parallelogram using microstrip line portion length L = 25.6 mm radiator and width of rationing lf = 8 mm. Second, the greater the length of the antenna radiator then lower the operating frequency and vice versa. The width of rationing affect the size of the antenna input impedance of the greater width of rationing, the input impedance is getting smaller, and vice versa. Third, the antenna dimensions are used to determine the model of the desired antenna characteristics resulting operating frequency of 5 GHz with the reflection coefficient -35.33 dB, 48.59 Ω input impedance and VSWR of 1.035